Polotsk neo-scholasticism vs I. Kant - Klimovich, Anna I. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The article carries out historical and philosophical reconstruction of I. Kant’s creative heritage reception in the works written by the Polotsk Jesuit Academy representatives J. Angiolini and W. Buczyńsky. There are revealed the main reasons for this authors to appeal to Kantian philosophy. It is also analysed, in which way the attempt to «read» Kantian philosophy in the philosophical courses of the mentioned academy was made. The emphasis is on the logical and metaphysical aspects, within the framework of which J. Angiolini and W. Buczyńsky most often criticised the ideas of transcendental idealism. The programme guidelines of scholastic philosophy are highlighted, which allowed the authors under consideration to try to overcome the difﬁculties of I. Kant’s philosophy. The scholastic philosophy programmatic guidelines, allowed the authors to try to overcome the difﬁculties of philosophy of I. Kant, are highlighted. It is also determined the place and role of the Kantian ide as reception, made by Polotsk philosophers and theologians, in the philosophical processes of the historical and cultural space of Belarus in the 19th century.